Memristive effects in oxygenated amorphous carbon nanodevices. (13th December 2017) - Bachmann, T A; Koelmans, W W; Jonnalagadda, V P; Le Gallo, M; Santini, C A; Sebastian, A; Eleftheriou, E; Craciun, M F; Wright, C D
Abstract: Computing with resistive-switching (memristive) memory devices has shown much recent progress and offers an attractive route to circumvent the von-Neumann bottleneck, i.e. the separation of processing and memory, which limits the performance of conventional computer architectures. Due to their good scalability and nanosecond switching speeds, carbon-based resistive-switching memory devices could play an important role in this respect. However, devices based on elemental carbon, such as tetrahedral amorphous carbon or ta-C, typically suffer from a low cycling endurance. A material that has proven to be capable of combining the advantages of elemental carbon-based memories with simple fabrication methods and good endurance performance for binary memory applications is oxygenated amorphous carbon, or a-CO x . Here, we examine the memristive capabilities of nanoscale a-CO x devices, in particular their ability to provide the multilevel and accumulation properties that underpin computing type applications. We show the successful operation of nanoscale a-CO x memory cells for both the storage of multilevel states (here 3-level) and for the provision of an arithmetic accumulator. We implement a base-16, or hexadecimal, accumulator and show how such a device can carry out hexadecimal arithmetic and simultaneously store the computed result in the self-same a-CO x cell, all using fast (sub-10 ns) and low-energy (sub-pJ) input pulses.